Nano Online 2016
DOI: 10.1515/nano.bjneah.6.102
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modeling of lithium ion batteries: thermal aspects

Abstract: This article is part of the Thematic Series "Materials for sustainable energy production, storage, and conversion".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…Exploiting the electroneutrality condition (1), the specialization for the mobility tensor simplifies to (22) The free energy j diff (c a ) in a mixture depends on the composition of the mixture itself. 7 Guided by the numerical analyses in Refs. [1,2], where it was shown that concentration peaks amount to about 50% of the saturation limit, the modeling assumption is here taken that concentrations are sufficiently far from saturation to disregard energetic interactions in the solution yet not small enough to neglect the saturation contribution.…”
Section: Constitutive Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Exploiting the electroneutrality condition (1), the specialization for the mobility tensor simplifies to (22) The free energy j diff (c a ) in a mixture depends on the composition of the mixture itself. 7 Guided by the numerical analyses in Refs. [1,2], where it was shown that concentration peaks amount to about 50% of the saturation limit, the modeling assumption is here taken that concentrations are sufficiently far from saturation to disregard energetic interactions in the solution yet not small enough to neglect the saturation contribution.…”
Section: Constitutive Theorymentioning
confidence: 99%
“…In view of the perfect electroneutrality, Gauss law provides the necessary and sufficient equation to be solved for f at t ¼ 0: 6 As the free energy density j has been selected as the thermodynamic potential, no source of confusion between the ion mobility and the internal energy density u will arise henceforth. 7 The case of diluted (in the sense of [11]) solutions will be considered henceforth whereas other theories will be summarized in Appendices. 8 The role played by the non linear mobility tensor and by the free energy density at saturation in Fick's law (25) is further investigated in appendix C. 9 Boundary conditions (29a) and (29c) have been derived in Section 3.3 of [1].…”
Section: Governing Equations and Weak Formmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2011 to 2015, Latz and Zausch developed a thermodynamically consistent model guaranteeing that the laws of thermodynamics are not violated. Using nonequilibrium thermodynamic principles, Maxwell's equation, and Onsager relations, these authors derived species transport equations and suitable interfacial conditions for the thermal model .…”
Section: Electrochemical Models Of Batteriesmentioning
confidence: 99%
“…Furthermore, effective transport parameters need to be determined to account for the influence of the microstructure on the average species transport. While these models are able to describe the average battery behavior surprisingly well [61,10,12,33], they cannot be expected to capture local microscopic effects. In particular, many degradation effects like, for instance, lithium plating depend on the local environment.…”
Section: Introductionmentioning
confidence: 99%